Hydrogen Sulfide: A Gaseous Mediator and Its Key Role in Programmed Cell Death, Oxidative Stress, Inflammation and Pulmonary Disease - Zhixing Zhu; Xihua Lian; Madhav Bhatia (MDPI AG, 2022)
Hydrogen sulfide (H2S) has been acknowledged as a novel gaseous mediator. The metabolism of H2S in mammals is tightly controlled and is mainly achieved by many physiological reactions catalyzed by a suite of enzymes. Although the precise actions of H2S in regulating programmed cell death, oxidative stress and inflammation are yet to be fully understood, it is becoming increasingly clear that H2S is extensively involved in these crucial processes. Since programmed cell death, oxidative stress and inflammation have been demonstrated as three important mechanisms participating in the pathogenesis of various pulmonary diseases, it can be inferred that aberrant H2S metabolism also functions as a critical contributor to pulmonary diseases, which has also been extensively investigated. In the meantime, substantial attention has been paid to developing therapeutic approaches targeting H2S for pulmonary diseases. In this review, we summarize the cutting-edge knowledge on the metabolism of H2S and the relevance of H2S to programmed cell death, oxidative stress and inflammation. We also provide an update on the crucial roles played by H2S in the pathogenesis of several pulmonary diseases. Finally, we discuss the perspective on targeting H2S metabolism in the treatment of pulmonary diseases.